IDIOLEKTNING O‘RGANILISH TARIXIDAN - Isomiddinova Nargiza Jozilboy qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides information about the idiolect, a concept that has not been specifically studied in Uzbek dialectology. World dialectology deals with the study and development of idiolects. In Uzbek dialectology, the concept of idiolect should be clarified. It is said that idiolect is one of the most important issues in the world today.